The Role of Oxidative Stress in the Clinical Manifestations of Childhood Asthma. (4th July 2017) - Topic, Aleksandra; Francuski, Djordje; Nikolic, Aleksandra; Milosevic, Katarina; Jovicic, Snezana; Markovic, Bojan; Djukic, Mirjana; Radojkovic, Dragica
ABSTRACT: Introduction : The significance of oxidative stress in pathogenesis of childhood asthma was recognized, but its role in the clinical manifestations of disease is still unclear. Materials and Methods : The study was conducted in 96 asthmatic children. The urinary biomarker of oxidative stress, 8-oxo-7, 8-dihydro-2-deoxyguanosine (8-oxodG/creatinine) was determined by using HPLC-MS/MS. ELISA was performed to measure myeloperoxidase (MPO) and Cu, Zn- superoxide dismutase (Cu, Zn-SOD) in serum. Results : Logistic regression analysis revealed that female gender, tobacco smoke exposure, and increased 8-oxodG/creatinine were associated with risk for intermittent asthma, while the positive allergy test and increased Cu, Zn-SOD were associated with eczema in asthmatic children. Higher MPO ( p = 0.033), and percent of granulocytes ( p = 0.030) were found in severe persistent asthma in comparison to intermittent or mild persistent asthma. Conclusion : The main findings that TSE-induced oxidative stress is a risk for intermittent asthma and eczema may be clinically significant for the disease prevention and therapeutic improvements.